(untitled) (Journal of Scientific Research, 2024)
An ionic liquid tagged schiff base, [1-2-(2-hydroxybenzylideneamino)ethyl-3-methylimidazolium]PF6 was synthesized from a functionalized ionic liquid (FIL) 2-aminoethyl-3-methylimidazolium hexafluorophosphate, [2-aemim]PF6 and salicylaldehyde without using any organic solvent. The Schiff base was used as a ligand to trap Mn(II), Co(II), Cu(II) ions from its corresponding metal acetates and to form the new transition metal complexes. The synthesized Mn(II), Co(II), Cu(II) complexes along with the Schiff base were characterized by ESI-MS, PXRD, UV-Visible, FT-IR, 1H NMR spectroscopic and analytical (elemental analysis and magnetic susceptibility measurements) methods. Based on these spectral analysis data tetra coordinated geometries were assigned for the newly synthesized metal(II) complexes. Antibacterial sensitivity of the Schiff base and the Mn(II), Co(II), Cu(II) complexes were evaluated against gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria to assess their minimum zone of inhibition.